Dampak Jahalah Terhadap Keabsahan Akad Jual-Beli - Fatih Fuadi (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2017)
The principle and the basic law of muamalah is permissible, unless there is a proof that does not allow it. It is also in transaction activities muamalah. However, there are many transaction of muamalah become damaged due to several things, among others the element of uncertanty (jahalah). This literature research using content analysis to provide information related of jahalah. The conclution of this article that every jahalah can lead to disputes that damage the contract that has been agreed between both parties. According to Hanafiah scholars there are several forms of bai’ al-fasiq, among the the jahalah. Jahalah has three levels namely jahalah fakhisyah, jahalah yasirah and jahalah mutawashittah. It is conclude inthis study that any muamalah contact containing the elemant of the jahalah is invalid or void. It depends to the principle of transparency, prudence and avoidence of damage (mafsadat) in muamalah.